Masculine interests : homoerotics in Hollywood films - Lang, Robert, 1957- (Film and culture., 2002)
Until Masculine Interests not much had been written about men "as men" in the cinema. Using nine Hollywood genre films from 1932 to the late 1990s, Lang shows how Hollywood's chief function to define, codify, valorize and critique varieties of masculinity reveals contradictions with its surface norms of heterosexual masculinity, particularly in those films that cover the troubled terrain of male-male relationships. Despite Hollywood's normative narrative conventions, these films involve a spectrum of primary bonds among men, sexual and nonsexual, conscious and unconscious. Lang questions the way our culture distinguishes between homosexuality and non-homosexual forms of male bonding, and argues for a more complex notion of a homosocial continuum